Proceedings of the Inter-Center Seminar on International Agricultural Research Centers (IARCs) and Biotechnology, 23-27 April 1984. (Manila, Philippines, 1985)
The proceeding collects papers presented at the Inter-Center Seminar on International Agricultural Research Centers (IARCs) and Biotechnology, 23-27 April 1984. The content varieties with a broad spectrum of resistance to pests and diseases, tolerance for adverse soil factors, and greater genetic capacity to utilize soil nitrogen. Second, they work on home-grown substitutes for market-purchased inputs such as fertilizers and pesticides. Third, they standardize techniques for maximizing returns from purchased inputs such as mineral fertilizers. Biotechnology offers scope for adding a dimension of resource neutrality in technology development.
Keywords: Agricultural biotechnology,Agricultural biotechnology,Agriculture; Congresses.,Research,International cooperation,Congresses.,Research,International cooperation,Congresses